PENGARUH APLIKASI PUPUK KOMPOS DAN BIOCHAR TERHADAP POPULASI BAKTERI DI RIZOSFER DAN PERTUMBUHAN TANAMAN PADI GOGO (Oryza sativa L.) - wati, Mifatun Rahma; Susilowati, Lolita Endang; Arifin, Zaenal (AGROTEKSOS; Vol 33 No 1 (2023): Jurnal Agroteksos April 2023DO - 10.29303/agroteksos.v33i1.820, 2023)
This study aims to examine the effect of the application of compost and biochar on the bacterial population in the rhizosphere and the growth of upland rice (Oryza sativa L.). and analysis of chemical and biological properties in the laboratory of chemistry and soil fertility, Faculty of Agriculture, University of Mataram. The soil used in this study had a pH value of 5.0 and available-P had 0.95 ppm, total N was 0.19%, K-exchanged was 0.22 meq/100g. C-organic value is only 1.2% and cation exchange capacity value (17.43 meq/100 g soil). the administration of doses of urea and phonska fertilizers combined with the provision of compost and biochar had an effect on the variables of plant height, number of tillers and leaf width where the P1 treatment gave a significant value compared to the P0 and P2 treatments. Parameters of root weight and stem weight in treatment P1 were more significant than those in treatment P0 and P2. In the variable total microorganisms with the number of bacterial colonies, phosphate solubilizing bacterial colonies and phosphate solubilizing fungal colonies had a significant value in the P1 treatment, in the respiration parameters of microorganisms p1 had a significant value with an average value of 4.36 mg C-CO2 / g soil.